Risk Factors and Clinical Characteristics of Congenital Primary Hypothyroidism: A Case-control Study in Ulaanbaatar, Mongolia - Tsevgee, Altantuya; Munkhchuluun, Tsolmon; Nansal, Gerelmaa; Khurelbaatar, Naranchimeg; Zagd, Gerelmaa; Ganbaatar, Erdenetuya (Central Asian Journal of Medical Sciences, 2021)
Objective: The study aimed to identify the risk factors and clinical features of congenital primary hypothyroidism (CPH). Methods: A matched case-control study recruited all children diagnosed with congenital primary hypothyroidism and children without disease as a control between 2012 and 2020. Controls were matched on their gender and age. We collected information on demographic, clinical, and laboratory characteristics from patient’s medical records. Results: The birth weight (OR = 1.1; p = 0.001), gestational age (OR = 2.24; p < 0.001), maternal age (OR = 1.21; p < 0.001), additional congenital disabilities (OR = 1.1; p = 0.015) and maternal hyperthyroidism (OR = 1.21; p < 0.011) were significant factors for CPH. The baby’s height (OR = 0.2; p = 0.012), maternal gestational diabetes (OR = 0.2; p = 0.002) and being a twin (OR = 0.91; p = 0.010) were significant protective factors for CPH. In terms of clinical symptoms of CPH, 70.2% had shown no clinical signs at births in our study. The most commonly identified clinical signs were: umbilical hernia, open posterior fontanel, feeding difficulty, hypothermia, abdominal stiffness, cold or mottled skin, prolonged jaundice, and low muscle tone. Conclusion: Children with CPH are often symptom-free at birth, and several risk factors contribute to CPH.